Does culture travel? Cultural influences on environmentalism in Taiwan in comparison to the United States. Issue 3 (3rd May 2020) - Liu, Li-Yin
Abstract: This study investigates how the grid-group two-dimensional cultural theory (CT) of Douglas and Wildavsky, demographic attributes, and partisan identification are associated with environmentalism in Taiwan, in comparison to the Weather, Society, and Government survey collected in the United States. Results reveal that partisan identification better explains environmental attitudes and concerns in Taiwan, but its explanatory power is not comprehensive. Gender and age explain environmental concerns in Taiwan but not environmental attitudes. The impact of CT on environmentalism appears in the Taiwanese environmentalist's group but not in the public, whereas CT has satisfactory power in explaining environmentalism in the United States.